Dietary Nitrate Provides Sustained Blood Pressure Lowering in Hypertensive Patients. Issue 2 (February 2015) - Kapil, Vikas; Khambata, Rayomand S.; Robertson, Amy; Caulfield, Mark J.; Ahluwalia, Amrita
<x xml:space="preserve">Abstract</x> Abstract— Single dose administration of dietary inorganic nitrate acutely reduces blood pressure (BP) in normotensive healthy volunteers, via bioconversion to the vasodilator nitric oxide. We assessed whether dietary nitrate might provide sustained BP lowering in patients with hypertension. We randomly assigned 68 patients with hypertension in a double-blind, placebo-controlled clinical trial to receive daily dietary supplementation for 4 weeks with either dietary nitrate (250 mL daily, as beetroot juice) or a placebo (250 mL daily, as nitrate-free beetroot juice) after a 2-week run-in period and followed by a 2-week washout. We performed stratified randomization of drug-naive (n=34) and treated (n=34) patients with hypertension aged 18 to 85 years. The primary end point was change in clinic, ambulatory, and home BP compared with placebo. Daily supplementation with dietary nitrate was associated with reduction in BP measured by 3 different methods. Mean (95% confidence interval) reduction in clinic BP was 7.7/2.4 mm Hg (3.6–11.8/0.0–4.9, P<0.001 and P=0.050). Twenty-four-hour ambulatory BP was reduced by 7.7/5.2 mm Hg (4.1–11.2/2.7–7.7, P<0.001 for both). Home BP was reduced by 8.1/3.8 mm Hg (3.8–12.4/0.7–6.9, P<0.001 and P<0.01) with no evidence of tachyphylaxis over the 4-week intervention period. Endothelial function improved by ≈20% (P<0.001), and arterial stiffness was reduced by 0.59 m/s (0.24–0.93; P<0.01) after dietary nitrate consumption with no change after placebo. The intervention was well tolerated. This is the first evidence of durable BP reduction with dietary nitrate supplementation in a relevant patient group. These findings suggest a role for dietary nitrate as an affordable, readily-available, adjunctive treatment in the management of patients with hypertension (funded by The British Heart Foundation). Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT01405898.